STUDI KOMPERATIF ANTARA PENDAPAT IMAM SYAFI’I DAN IMAM MALIKTENTANG PENGAMBILAN BUAH POHON PADA BARANG GADAI TANAH (Studi di Kecamatan Guluk-guluk Kab. Sumenep) - Mondzir, Mondzir; Thohari, Chamim (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
ABSTRACT        This study entitled "a comparative study of Imam Syafi'i and Imam Malik's opinion on Taking Fruit Trees on Land Pawn Goods (Case Study in Guluk-guluk District, Sumenep Regency). The pawning party generally gives the pawn party the land with the fruit of the tree to the pawn recipient and must give the fruit of the tree to the pawn recipient until the pawner pays the debt.       The research method used in this study is the field research method (Case Study) also intended to study intensively about the background of the current situation, as well as the specific social unit environmental interactions that are (given).       The results of this study regarding the taking of fruit trees on earthly pawned goods carried out by the Guluk-guluk District community according to Imam Syafi'i the fruit of the tree is not part of the pawning goods (marhun bih) but the fruit is the property of the mortgaged person (ar-Raahin ). Meanwhile, according to Imam Malik, the law is permissible if it is used as a pawn condition. Key Words : ar-Rahn, ar-Rahin, al-Murtahin, al-Marhun, al-Marhun bih.